Spin splitting of dopant edge state in magnetic zigzag graphene nanoribbons - Blackwell, Raymond E.; Zhao, Fangzhou; Brooks, Erin; Zhu, Junmian; Piskun, Ilya; Wang, Shenkai; Delgado, Aidan; Lee, Yea-Lee; Louie, Steven G.; Fischer, Felix R. (Nature (London), 2021)
Spin-ordered electronic states in hydrogen-terminated zigzag nanographene give rise to magnetic quantum phenomena 1 , 2 that have sparked renewed interest in carbon-based spintronics 3 , 4 . Zigzag graphene nanoribbons (ZGNRs)—quasi one-dimensional semiconducting strips of graphene bounded by parallel zigzag edges—host intrinsic electronic edge states that are ferromagnetically ordered along the edges of the ribbon and antiferromagnetically coupled across its width 1 , 2 , 5 . Despite recent advances in the bottom-up synthesis of GNRs featuring symmetry protected topological phases 6 – 8 and even metallic zero mode bands 9 , the unique magnetic edge structure of ZGNRs has long been obscured from direct observation by a strong hybridization of the zigzag edge states with the surface states of the underlying support 10 – 15 . Here, we present a general technique to thermodynamically stabilize and electronically decouple the highly reactive spin-polarized edge states by introducing a superlattice of substitutional N-atom dopants along the edges of a ZGNR. First-principles GW calculations and scanning tunnelling spectroscopy reveal a giant spin splitting of low-lying nitrogen lone-pair flat bands by an exchange field (~850 tesla) induced by the ferromagnetically ordered edge states of ZGNRs. Our findings directly corroborate the nature of the predicted emergent magnetic order in ZGNRs and provide a robust platform for their exploration and functional integration into nanoscale sensing and logic devices 15 – 21 . Decoupling spin-polarized edge states using substitutional N-atom dopants along the edges of a zigzag graphene nanoribbon (ZGNR) reveals giant spin splitting of a N-dopant edge state, and supports the predicted emergent magnetic order in ZGNRs.